MENGOMUNIKASIKAN KETELADANAN PANJI: Apresiator Kompleks dalam Budaya Etnik, Era Digital, Regulasi Kebudayaan - henricus supriyanto (Jurnal Budaya Nusantara, 2018)
The current proposed discussion is related to the complexity that is analyzed based on the stage of thinking.This happens because the current turn of the era which 'back and forth' turns out into a cultural cross. Not monitoredin detail, followed by a changing educational system, and not necessarily in tune with the needs and expectations ofgenerations of "X" and "Y" in the present. In this connection, the idea of harmony can be learned from variousfolklore, which is common in speech stories or by using role models with the following characteristics; 1) always presentas the savior of the kingdom, 2) a consistent figure in the family (in the world of love and the protection of hisgeneration), 3) the original figure of the archipelago earth, not imported figures. All three of these are in the story / play-story of Folk Art Performing/Panji Tradition. Apresiator Mapping in the Digital Age Culture today and thefuture will be more complex, because it can not be separated from non-cultural factors, such as industry, economics,politics and technology. Therefore, the birth function of Review on Transfer Modes based on consideration is to observethe development of digital technology and information technology, increasingly supporting the transformation (Budiman,2012: ii). Considering ethnic and sub ethnic cultures, the digital age, the transfer of modes and regulations of"Cultural Progress", communicating the Panji Oral Tradition can be carried out as follows; 1) Direct or face-to-facecommunication, by way of storytelling, staging folk/traditional performances, effective in 3 T areas (disadvantaged,leading, marginalized) 2) Media communication, 3) Communication in modern areas/no communication systembarriers.